New Hierarchical Routing Protocol Based on K-Means Clustering with Exploiting Free Time Slot for Wireless Sensor Networks - Echoukairi, Hassan; Idrissi, Abdellah; Omary, Fouzia (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The operation time of LEACH protocol is divided into several frames. Each frame consists of a number of equal time slots where the selection of cluster heads and the re-establishment of clusters are periodic. Each member of the cluster exploits its own time slot to transmit the data, then it turns off its radio to reduce energy consumption. Here, the clusters generated are not uniformly distributed and the time slots of the dead member nodes are not allocated. We propose an improved version, which is based simultaneously on the integration of the clustering approach K-Means and the exploitation of the free time slot in favor of cluster head in the transmission phase. The results show that the proposed protocol allowed us to achieve increased throughput, improved reliability of the packet delivery ratio, low routing load and an effective reduction in energy consumption for low node density in WSNs.